Pengaruh Metode Demonstrasi untuk Meningkatkan Kemampuan Baca Tulis Arab Melayu (Jawi) di Madrasah Tsanawiyah - Laila Vina Lita; Sri Mawaddah (Hikmah : Jurnal Studi Pendidikan Agama Islam, 2025)
Demonstration method in improving the ability to read and write Arabic Malay (Jawi) in Madrasah Tsanawiyah. Arabic Malay writing is a cultural heritage of the Archipelago that is important to preserve, especially in Islamic education environments. The demonstration method combined with lectures and demonstration methods allows students to learn concretely through direct explanations and demonstrations, so that they are able to understand the letter forms, pronunciation, and structure of Arabic Malay writing better. This study found that the demonstrative approach gave positive results in improving students' ability to read and write Arabic Malay, and was an effective method in fostering interest in learning and preserving local cultural scripts.